Positive solutions for (p, q)-equations with convection and a sign-changing reaction - Zeng Shengda (De Gruyter, 2021)
We consider a nonlinear Dirichlet problem driven by the (p, q)-Laplacian and with a reaction which is dependent on the gradient. We look for positive solutions and we do not assume that the reaction is nonnegative. Using a mixture of variational and topological methods (the "frozen variable" technique), we prove the existence of a positive smooth solution.